2008
DOI: 10.1029/2008gl036077
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind proton reflection at the lunar surface: Low energy ion measurement by MAP‐PACE onboard SELENE (KAGUYA)

Abstract: Interaction between the solar wind and objects in the solar system varies largely according to the settings, such as the existence of a global intrinsic magnetic field and/or thick atmosphere. The Moon's case is characterized by the absence of both of them. Low energy ion measurements on the lunar orbit is realized more than 30 years after the Apollo period by low energy charged particle analyzers MAP‐PACE on board SELENE(KAGUYA). MAP‐PACE ion sensors have found that 0.1%∼1% of the solar wind protons are refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
182
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(205 citation statements)
references
References 24 publications
17
182
0
Order By: Relevance
“…• Specular reflection from the lunar surface has been observed to accelerate solar wind ions to three times that of the bulk plasma velocity [Saito et al, 2008]. This is however judged unlikely at Rhea due to high water-group photodetachment rates in Saturn's magnetosphere [Coates et al, 2010] precluding negatively charged O − existing in abundance as an ambient magnetospheric population.…”
Section: Velocity Space Analysismentioning
confidence: 99%
“…• Specular reflection from the lunar surface has been observed to accelerate solar wind ions to three times that of the bulk plasma velocity [Saito et al, 2008]. This is however judged unlikely at Rhea due to high water-group photodetachment rates in Saturn's magnetosphere [Coates et al, 2010] precluding negatively charged O − existing in abundance as an ambient magnetospheric population.…”
Section: Velocity Space Analysismentioning
confidence: 99%
“…Even outside of the influence of crustal fields, we now know that part of the solar wind ion population reflects from the surface, in both ion (Saito et al, 2008) and more often in neutral form (Wieser et al, 2009;McComas et al, 2009). The dayside lunar surface also provides a source of low energy photoelectrons produced by solar photons and secondary electrons produced by both electron and ion impact, as well as reflected and backscattered primary electrons (Feuerbacher et al, 1972;Willis et al, 1973;Whipple, 1981;Horányi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This sputtering erodes surface grains at a rate of 0.01-0.04 nm/yr [e.g., Wehner et al, 1963;Johnson and Baragiola, 1991], however, the porous nature of the regolith may trap >90% of forward-directed sputtered species [Hapke, 1986]. Ion sensors onboard the SELENE spacecraft in lunar orbit recently detected backscattered solar wind particles and found that $0.1-1% of the solar wind protons bombarding the lunar surface backscatter from the Moon as ions [Saito et al, 2008]. During the backscatter process, however, incident solar wind ions are mostly neutralized, and the vast majority should exit as ENAs with a broad distribution of energies up to the solar wind energy.…”
Section: Introductionmentioning
confidence: 99%